2016
DOI: 10.1021/acs.chemmater.6b00165
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Low Concentration of Dopants on the Distribution of Gap States in a Molecular Semiconductor

Abstract: We investigate the distribution of valence and tail states in copper phthalocyanine (CuPc) upon the introduction of minute amounts of the p-dopant molybdenum tris[1,2-bis-(trifluoromethyl)ethane-1,2-dithiolene] (Mo(tfd) 3 ), using a combination of electron spectroscopy and carrier transport measurements. Density of gap states, conductivity, and hole-hopping activation energy are measured. We observe the progressive filling (and deactivation) of the deepest tail states by charges introduced by the dopants, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 28 publications
4
43
0
Order By: Relevance
“…E a decreases from 0.29 to 0.24 eV with as little as 1.0 mol% F6-TCNNQ, and further to 0.18 eV with 10.0 mol%. In analogy to previous work on n-doping of C 60 [33] and p-doping of CuPc, [25] this evolution is attributed to the filling and deactivation of trap and tail states by holes generated from the F6-TCNNQ molecules. As more dopants are introduced, E F moves toward the Spiro-TAD HOMO into a region of higher density of states where the activation energy for the hopping process is lower.…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…E a decreases from 0.29 to 0.24 eV with as little as 1.0 mol% F6-TCNNQ, and further to 0.18 eV with 10.0 mol%. In analogy to previous work on n-doping of C 60 [33] and p-doping of CuPc, [25] this evolution is attributed to the filling and deactivation of trap and tail states by holes generated from the F6-TCNNQ molecules. As more dopants are introduced, E F moves toward the Spiro-TAD HOMO into a region of higher density of states where the activation energy for the hopping process is lower.…”
Section: Introductionsupporting
confidence: 62%
“…Lin et al reported increased disorder in CuPc films doped with Mo(tfd) 3 . [25] Doping-induced change in morphology was also reported for solution processed polymer thin films, such as poly(3-hexylthiophene) (P3HT). Duong et al [26] directly visualized the dopant distribution in P3HT:F4-TCNQ blend films using conductive atomic force microscopy (C-AFM), and showed that both dopant distribution and film morphology depend on the strength of the doping process.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…[ 40 ] External quantum effi ciency measurements were performed using a Newport TLS-300X tunable light source system. Ultraviolet photoelectron spectroscopy and inverse photoelectron spectroscopy were used to characterize the electronic structure of each fi lm, using a setup described elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…This undesired consequence is often observed in the distinct case of dopants, which are chosen for their ability to directly tune the electronic properties, rather than for their similarity in chemical structure to the host. Since doping in organic‐semiconductor systems is far less efficient than in the inorganic systems from which the technique was borrowed, dopant molar concentrations in excess of 1% are often required to effect the desired electronic changes in the host material . At such high concentrations, the anticipated electronic benefits of doping are often thwarted by insufficient consideration of the structural compatibility of the dopant and host material.…”
mentioning
confidence: 99%